Effects of sterilization, humic acid and indigenous microbial formulation on physicochemical properties and macro micronutrients of dairy farm effluent compost - Edelisa Jenny Radius; Evernessah Eva Dominus; Chong, Khim Phin; Syahriel Abdullah; Januarius Gobilik (e-VIBS, Faculty of Science and Natural Resources, 2024)
Biostimulant application can enhance compost’s physicochemical properties, nutrient content and performance. Dairy farm effluent compost (DFEC) is a promising planting medium for leafy vegetable production. However, little is known about its quality after biostimulant application. The present study was carried out to evaluate the effects of humic acid (HA) and indigenous microbial formulation (IMF) on DFEC’s physicochemical properties and macro-micronutrients. Sterilised (ST) or non-sterilised (NST) DFECs were added with HA, IMF or NPK 15:15:15 fertiliser, or a combination of them; there were eight amendments (A1-A8). The amended DFECs were re-used four times for Pak Choy cultivation; the plants were planted in forty-eight 18 L pots. DFEC samples were collected from each pot at the second (MR2), third (MR3) and fourth (MR4) harvesting of the Pak Choy, and the physicochemical properties (pH, EC, C/N ratio, OM, OC, WHC) and macro-micronutrients (N, P, K, Mg, Ca, Na, Mn, Fe, Zn and Cu) were evaluated. The macro-micronutrients were analysed using a CHN analyser and ICP-OES. The data were analysed by performing threeway ANOVA at  = 0.05 using SAS. ST-DFEC had higher pH, EC, C/N ratio, WHC, and macro-micronutrients (P, K, Ca, Na, Mn, Fe, and Cu) but lower OM and OC. HA, IMF or HA+IMF application did not significantly affect the DFEC’s physicochemical properties and macro-micronutrients. The effects were significant only after NPK addition (A5-A8). HA+IMF+NPK (A8) was the best amendment to improve P, K, Ca, Na, Mn, Fe, and Cu levels. Nutrient content was better in the second and fourth re-usage of the compost. The data indicated that DFEC’s agronomic quality could be improved by sterilization, NPK+HA+IMF addition or NPK and at least one of the biostimulants, re-usage with NPK and biostimulant applications, or a combination of those amendments.